Awareness, attitudes towards genetic diseases and acceptability of genetic interventions among pregnant women in Burera district, Rwanda - Jean Baptiste Niyibizi; Erigene Rutayisire; Monica Mochama; Michael Habtu; Zephanie Nzeyimana; Daniel Seifu (BMC, 2023)
Abstract Approximately 3% of all pregnancies are associated with conditions linked with disability, either mild or severe congenital diseases. This is a consequence of environmental and genetic exposures. Complications and poor management of these diseases arise due to limited knowledge, awareness about the disease, and limited resource settings. The current study assessed awareness, attitudes towards genetic diseases, and acceptability of genetic interventions among pregnant women. This was a cross-sectional study that was conducted among 664 pregnant women in six selected health centers in Burera district using a detailed questionnaire. The data were analysed using STATA Version 15 and entailed univariate, bivariate, and multivariable analyses. The level of significance was set at p < 0.05. The mean age of the study participants was 28, and most of them were in the age range of 21 to 30 (50%). Most of the participants were married (91.1%), Christians (98.4%), farmers (92.7%), used public health coverage (96.6%), and attained primary studies (66.1%). The findings from this study showed that among participants, adequate awareness was at 29.5%, inadequate awareness at 70.5%, positive attitudes at 87.1%, negative attitudes at 12.9%, high acceptability at 97.1%, and low acceptability at 2.9%. While there was no significant difference between awareness and acceptability, there was a statistical significance between attitudes towards genetic diseases and acceptability towards the use of genetic services (p < 0.01). There was no statistical significance between sociodemographic or obstetric characteristics and the acceptability of genetic interventions. Participants with positive attitudes towards genetic diseases were more likely to develop a high level of acceptability and willingness towards the use of genetic interventions (OR: 5.3 [2.1-13.5]). Improving awareness about genetic diseases and establishing genetic interventions in healthcare facilities are needed.